Association between hemoglobin-to-red blood cell distribution width ratio and hospital mortality in patients with non-traumatic subarachnoid hemorrhage - Liu, Jiuling; Wang, Junhong (Frontiers in Neurology, 2023)
Background: In patients with ischemic stroke, low hemoglobin-to-red cell distribution width ratio (HRR) was associated with an increased risk of mortality. However, it was unknown in the non-traumatic subarachnoid hemorrhage (SAH) population. The purpose of this study was to examine the association between baseline HRR and in-hospital mortality in patients with non-traumatic SAH. Methods: Non-traumatic SAH patients were screened out of the Medical Information Mart for Intensive Ⅳ (MIMIC-Ⅳ) database between 2008 and 2019. The Cox proportional hazard regression models were utilized to analyze the association between baseline HRR and in-hospital mortality. Restricted Cubic Splines (RCS) analysis was utilized to determine the relationship curve between hospital mortality and PP level and examine the threshold saturation effect. We further applied Kaplan-Meier survival curve analysis to examine the consistency of these correlations. The interaction test was used to identify subgroups with differences. Results: A total of 842 patients were included in this retrospective cohort study. Compared with individuals with lower HRR Q1 (≤ 7.85), the adjusted HR values in Q2 (7.86-9.15), Q3 (9.16-10.16), and Q4 (≥ 10.17) were 0.574 (95% CI: 0.368-0.896, p = 0.015), 0.555(95% CI: 0.346-0.890, p = 0.016), and 0.625 (95% CI: 0.394-0.991, p = 0.045), respectively. The association between HRR level and in-hospital mortality exhibited a non-linear relationship (p < 0.05). The threshold inflection point value of 9.50 was calculated using RCS analysis. When the HHR level was lower than 9.50, the risk of in-hospital mortality rate decreased with an adjusted HR of 0.79 (95% CI: 0.70-0.90, p = 0.0003). When the HRR level was higher than 9.50, the risk of in-hospital mortality almost hardly increased with the increase in HRR level (adjusted HR = 1.18, 95% CI: 0.91-1.53, p = 0.2158). K-M analysis showed that patients with low HRR levels had significantly higher in-hospital mortality (p < 0.001). Conclusion: There was a non-linear connection between the baseline HRR level and in-hospital mortality. A low level of HRR could increase the risk of death in participants with non-traumatic SAH.